Hong Kong leftist cinema in the Cold War era: In-betweenness, sensational success and censorship. Issue 1 (2nd January 2019) - Du, Ying
Abstract: Using Shanghai archives supplemented by US and Hong Kong archives, this paper explores the complex circumstances of Hong Kong's leftist cinema – from its cultural identification to its production and distribution – within the PRC's context of both tightening and sometimes relaxing its controls over films, and the international context of the cinematic Cold War between mainland China, the United States and Taiwan. It shows how Hong Kong's leftist cinema built up an 'in-between' identity by conflating entertainment and edification, PRC concerns and the Hong Kong experience, and how it struggled to survive the multiple political confinements imposed by the Hong Kong government and the US and Taiwanese powers in Hong Kong, and the PRC's periodic policies in the 1950s and 1960s. This paper argues that the dynamics of Hong Kong leftist cinema came from their dislocated position in both the socialist system/mainland China and the capitalist system/Hong Kong; meanwhile Hong Kong leftist cinemas' difficulties lay in the border-crossing limits between the two systems.